Le peintre graveur : Vol. XVIII-XXII Maîtres Italiens (suite) - Suppléments - Bartsch, Adam, (European History and Culture - Book Archive pre-2000., 1982)
The print edition is available as a set of four volumes (9789060042571). Small-size reprint of the 22 vols. of this famous standard work in reduced form: each page of the reprint containing four pages of the original. Vols. I-IV: Dutch (and Belgian) artists; V-XI: German artists; XII-XXI: Italian artists; XXII: Supplements. See Less